Fast Analysis of Puerarin and Daidzein in Radix puerariae and It’s Medicinal Preparation by Micellar Electrokinetic Capillary Chromatography - Jia1, K.; Wang2, J.; An3, K. (Asian Journal of Chemistry, 2013)
A method was developed to determine puerarin and daidzein in Radix puerariae and it's medicinal preparation Gegen qinlianpian by micellar eletrokinetic capillary chromatography. The analytical conditions were optimized by investigating the effects of buffer pH and concentration, sodium dodecyl sulfate concentration and b-cyclodextrin. Under the optimized conditions, the two analytes were well separated in 5 min. A good linear relationship between the peak height and concentration was found in the 0.02-1.20 and 0.02-1.00 mg mL-1 concentration range for puerarin and daidzein, respectively. The relative standard deviation based on migration time and peak height were 0.51 and 1.82 % for puerarin, 0.45 and 1.68 % for daidzein, respectively. The detection limits were 0.005 and 0.004 mg mL-1 for puerarin and daidzein, respectively.